Prediction of Post-operative Long-Term Outcome of the Motor Function by Multimodal Intraoperative Neuromonitoring With Transcranial Motor-Evoked Potential and Spinal Cord-Evoked Potential After Microsurgical Resection for Spinal Cord Tumors - Yamada, Shinsuke; Kawajiri, Satoshi; Arishma, Hidetaka; Isozaki, Makoto; Yamauchi, Takahiro; Akazawa, Ayumi; Kidoguchi, Masamune; Kodera, Toshiaki; Shibaike, Yoshinori; Umeda, Hideto; Tsukinowa, Yu; Hagihara, Ryota; et al. (Frontiers in Surgery, 2022)
Objective To examine the effect of multimodal intraoperative neuromonitoring on the long-term outcome of motor function after microsurgical resection for spinal cord tumors. Materials and Methods Consecutive fourteen patients with spinal tumors who were surgically treated at the University of Fukui Hospital between 2009 and 2020 [M:F = 10:4, ages ranging from 22 to 83 years (mean ± SD = 58 ± 21 years)] were included in this study. There were eight intra-axial tumors and six extra-axial tumors. There were four patients with hypertension, two patients with diabetes mellitus, and four patients with hyperlipidemia. Three patients were under antithrombotic medication, two were under steroid medication, four were current smokers, and four were current drinkers. Manual muscle test (MMT) of the upper and lower extremities of the patients was examined before surgery, 2 weeks after surgery, and at the final follow-up. The mean follow-up period was 38 ± 37 months. McCormick scores were examined before surgery and at the final follow-up. Microsurgical resection of the tumor was underwent through the posterior approach under transcranial motor-evoked potential (TcMEP) monitoring. The MEP of 46 extremities was recorded during the surgery. Gross total resection was achieved in 13 of 14 surgeries. Spinal cord-evoked potential (Sp-SCEP) monitoring was performed in eight of 14 patients. Results The length of peritumoral edema was significantly longer in patients with deterioration of McCormick scores than in patients with preservation of McCormick scores (p = 0.0274). Sp-SCEP could not predict the deterioration. The ratio of MEP at the beginning of the surgery to that at the end of the surgery was the only significant negative factor that predicts deterioration of motor function of the extremity at the final follow-up (p = 0.0374, odds ratio [OR] 1.02E-05, 95% CI 9.13E+01–7.15E+18). A receiver operating characteristic (ROC) analysis revealed that the cutoff value of the ratio of MEP to predict the deterioration at the final follow-up was 0.23 (specificity 100%, specificity 88%, positive predictive value 100%, and negative predictive value 88%) to predict deterioration at the final follow-up. Conclusions Ratio MEP was the most significant negative factor to predict the deterioration of motor weakness at spinal tumor surgery. The setting of the cutoff value should be more strict as compared to the brain surgery and might be different depending on the institutions.